Vibration reduction of Cable-Driven Parallel Robots through elasto-dynamic model-based control. (September 2019) - Baklouti, Sana; Courteille, Eric; Lemoine, Philippe; Caro, Stéphane
Highlights: Elasto-dynamic model-based control of Cable-Driven Parallel Robots (CDPRs). This control method combines a model-based feed forward control scheme for CDPRs with a PID feedback controller. The elasto-dynamic model of CDPR is used to anticipate its dynamic behavior, including vibratory effects and cable elongations. The effectiveness of the proposed elasto-dynamic control strategy is studied numerically and experimentally. The elasto-dynamic control leads to an improvement of 35% for the first Peak-to-Peak amplitude of the moving-platform with respect to the rigid control. Abstract: This paper deals with the elasto-dynamic model-based control of Cable-Driven Parallel Robots (CDPRs), which manifests in the coupling of a PID feedback controller with a model-based feed-forward control scheme. The feed-forward controller is derived from an inverse elasto-dynamic model of CDPR, which compensates the end-effector dynamics and specifically its vibrations due to cable elasticity. The integration of cable tension calculation into this control strategy guarantees positive cable tensions along the trajectory. Simulations and experimentations while using a suspended and non-redundant CDPR show that tracking errors and vibrations can be reduced by the proposed strategy compared to conventional rigid-body model-based control.